Klimadiagramme: Gedanken und Bemerkungen über die Verwendung von Klimadiagrammen für die Typisierung und den Vergleich von Klimaten - Lauer, Wilhelm (ERDKUNDE, 1960)
In climatology, diagrams are important in the elucidation of descriptive material and maps. They assist in the recognition of many causal connections and the establishment of climatic types. For investigations dealing with large areas temperature and precipitation diagrams are the most suitable for characterizing climate. Three different types of diagrams are usually distinguished: 1. The usual diagram (after A. Hettner) showing the course of precipitation and temperature throughout the year. 2. Climograms. 3. Humidity diagrams in which temperature and precipitation are expressed through an index. The two latter types of diagrams can also show rainy and dry seasons if the appropriate limit of dryness is entered. Gaussen, 1953, and Walter, 1955, have shown that the Hettner diagram may also be used for showing humid and dry seasons provided the P- and T-ordinates are entered in the proportion p = 2 t. This paper shows that the formula p = 2 t is not suitable for all types of climate and is only valid for those regions for which the authors mentioned developed this quotient. For the tropics especially, and also for zones characterized by an alternation between rainy and dry seasons, it is suggested that de Martonne' index of dryness should be used. In temperate climates, especially those where rain occurs at all seasons, and in boreal climates, it is the temperature which characterizes the weather over the year. An ombrothermic quotient which merely emphasizes dry and humid seasons is then of little use. In any case a world atlas of climatic diagrams, as suggested by Walter, would have to employ different indices to suit the different climates. Thus, though diagrams offer valuable assistance and a means of presentation for a classification of climates, they hold no new key to a solution.